Helminth infection levels on Rattus rattus (Rodentia: muridae) from Corrientes city, Argentina - Gómez Muñoz, María A. (2018)
The aim of this study was to describe the infection levels of helminths of Rattus rattus in Corrientes city, Corrientes Province, Argentina. In order to determine the role of rodents as potential reservoirs for zoonotic parasites, different indices of helminth infection were assessed with respect to sex, age, season and urban landscapes. A total of 107 individuals of R. rattus were examined. Seven species of helminths were found. The values of total prevalence, mean intensity and mean abundance were 68%, 20 and 13, respectively. Nippostrongylus brasiliensis was the species more prevalent and abundant. The results showed that the age of the rodents and the season of capture had effects on the helminth infection.